Pelatihan Sehat Keuangan dan Sadar Investasi bagi Para Nasabah Mikro kepada Para Pemimpin Unit Bank BRI di Purbalingga. - Eka Tripustikasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The public has not received much literacy about investment properly. Banks that are in contact with the public in relation to the economy should provide this literacy to the public. If the public has good knowledge of investment literacy, the higher the savings and return value obtained from the investment. Investment is a guarantee for the future against accidents, disasters or death. This training activity provides knowledge and an invitation to BRI Purbalingga branch unit leaders to be able to provide counseling and play an active role in inviting the public to invest. The more people care about investment, the greater the potential return of value obtained, and increasing can also be helped by the large amount of funds collected and which can be distributed to other activity units or programs.